Fungal Epithiodiketopiperazines Carrying α, β‐Polysulfide Bridges from Penicillium steckii YE, and Their Chemical Interconversion. (30th September 2020) - Jiang, Guangde; Zhang, Peilan; Ratnayake, Ranjala; Yang, Guang; Zhang, Yi; Zuo, Ran; Powell, Magan; Huguet‐Tapia, José C.; Abboud, Khalil A.; Dang, Long H.; Teplitski, Max; Paul, Valerie; et al.
Abstract: Some fungal epithiodiketopiperazine alkaloids display α, β‐polysulfide bridges alongside diverse structural variations. However, the logic of their chemical diversity has rarely been explored. Here, we report the identification of three new (2, 3, 8 ) and five known (1, 4 –7 ) epithiodiketopiperazines of this subtype from a marine‐derived Penicillium sp. The structure elucidation was supported by multiple spectroscopic analyses. Importantly, we observed multiple nonenzymatic interconversions of these analogues in aqueous solutions and organic solvents. Furthermore, the same biosynthetic origin of these compounds was supported by one mined gene cluster. The dominant analogue (1 ) demonstrated selective cytotoxicity to androgen‐sensitive prostate cancer cells and HIF‐depleted colorectal cells and mild antiaging activities, linking the bioactivity to oxidative stress. These results provide crucial insight into the formation of fungal epithiodiketopiperazines through chemical interconversions. Abstract : Chemical and functional diversity : Multiple new and known cytotoxic epithiodiketopiperazines containing α, β‐polysulfide bridges were produced by a Penicillium sp. isolated from a black band layer of a coral sample. These analogues originated from the same gene cluster but demonstrated nonenzymatic interconversions to afford chemical diversity.